Agriculture wastes and role of environmental law in Malaysia - Mustafa, Maizatun; Ariffin Ho, Mariani (2006)
The growth of agricultural sector and its significance in the overall economic development in Malaysia is becoming more evident especially in the recent years. However, agricultural practices inevitably cause various environmental issues, from the problem of land degradation to the discharge of agricultural wastes into the environment. Legal instrument has been known to be an important tool in dealing with environmental pollutants, including that of agricultural wastes. In Malaysia, Environmental Quality Act 1974 is considered to be the most comprehensive legislation pertaining to the environment, covering various aspects of environmental pollutants, and being applied to the whole of the country. However, while in reality agricultural wastes have been a relatively main component of environmental pollutants in Malaysia,this Act does not contain any specific provision on 'agricultural wastes' even though there exist several regulations under the Act pertaining to 'wastes' in general. Issues presented in this paper are possible legal factors responsible for a more effective control of agricultural wastes from the environmental point of view, and the possibilities that are more sustainable control of agricultural wastes by turning them into secondary raw materials is viable through the application of environmental law in Malaysia. For this purpose, this paper seeks to provide an overview of the existing provisions under the Environmental Act 1974 and other legislation relevant to the issue in question, to discuss limitations of the law and to highlight possible legal solution under the Malaysian environmental law towards a more sustainable regulation of agricultural wastes in the country.